Komunikasi Politik Bilhikmah Datuk Kalampayan Dan Relevansinya Dewasa Ini - M. Irpan; Sanusi; Didi Susanto (LPPM Universitas Bina Sarana Informatika, 2022)
This research aims to describe the political communication of bilhikmah Datuk Kalampayan in the Banjar Sultanate and its relevance today in South Kalimantan. This research was conducted using a qualitative method with a case study approach. Data collection techniques in the form of interviews, observations and documentation studies. The results showed that the political communication carried out by Sheikh Muhammad Arsyad al-Banjari known as Datuk Kalampayandi in the 18th century actually strengthened the theory of Mead's symbolic intracional communication in the 19th century, Secondly, Datuk Kalampayan's political communication model in the Banjar sultanate contributed to the discipline of communication; The political Communication Model carried out was: the Bilhikmah Political Communication Model, with characteristic values, including; Strengthening the firmness of faith as the foundation of life in society, nation and state. Upgrading oneself (science and charity), consistent coexistence, harmonious synergy. Don't do any criticism